UM OLHAR SOBRE A TRAJETÓRIA DO MUSEU DE CIÊNCIA RICARDO FERREIRA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
In this study, which is characteristic of qualitative research, we discuss the theoretical, methodological and trajectory of the Ricardo Ferreira Science Museum - MCRF, based on discussions held in the Master in Science Education: Chemistry of Life and Health at the Federal University of Rio Grande of the South – UFRGS. The Museum is located at the State Reference School Otacílio Nunes de Souza (EREMONS), Petrolina, in the hinterland of Pernambuco. One of the objectives is to try to answer the following problem: how can scientific education and science popularization activities, based on Freirean precepts, contribute to the scientific culture and science teaching of young students and teachers from the school community in question? MCRF was founded in 2012, in 2015, it became part of the school's Political Pedagogical Project, which is full-time education. The text is organized in theoretical discussions, actions, analysis of the path and trajectory of the MCRF, in a discussion about the perspective of a non-formal space within a high school of basic education. The construction of a non-formal space, with the pedagogy of the question, generative themes and dialogicity in Freire, has provided the learning of young students, through arguments, as well as conflicts and the construction of scientific concepts, previously considered tragic.
Keywords: Scientific Education; Scientific Dissemination; Non Formal Education